Control of Drinking Water by Linking Biosensors with Physicochemical Methods. (2015) - Cimalla, V.; Hugger, S.; Fuchs, F.; Anzt, J.; Bitterling, M.; Yang, N.; Kohl, C.; Maucher, T.; Mühlemeier, I.; Burger-Kentischer, A.; Trick, I.
Abstract: An alarm system is developed for the direct detection of toxic substances in drinking water. The vitality of living organisms or cells is monitored continuously by electrochemical and infrared spectroscopic methods. Mammalian cells or bacteria are acting as highly sensitive biosensors and are monitored simultaneously by infrared and electrochemical techniques. It enables the non-specific detection of toxins with short response times for implementation in water supplies.